Efficacy of bergamot: From anti‐inflammatory and anti‐oxidative mechanisms to clinical applications as preventive agent for cardiovascular morbidity, skin diseases, and mood alterations. Issue 2 (25th January 2019) - Perna, Simone; Spadaccini, Daniele; Botteri, Leonardo; Girometta, Carolina; Riva, Antonella; Allegrini, Pietro; Petrangolini, Giovanna; Infantino, Vittoria; Rondanelli, Mariangela
Abstract: We summarize the effects of bergamot (extract, juice, essential oil, and polyphenolic fraction) on cardiovascular, bone, inflammatory, skin diseases, mood alteration, anxiety, pain, and stress. This review included a total of 31 studies (20 studies on humans with 1709 subjects and 11 in animals (rats and mice)). In humans, bergamot‐derived extract (BE) exerts positive effects on hyperlipidemia with an oral dose from 150 mg to 1000 mg/day of flavonoids administered from 30 to 180 days, demonstrating an effect on body weight and in modulating total cholesterol, triglycerides, LDL, and HDL. Studies in animals confirm promising data on glucose control (500/1000 mg/day of BE with a treatment lasting 30 days) are available in rats. In animals models, bergamot essential oil (BEO, 10 mg/kg or 20 mg/kg daily for 20 weeks) increases bone volume, decreases psoriatic plaques, increases skin collagen content, and promotes hair growth. Bergamot juice (20 mg/kg) is promising in terms of pro‐inflammatory cytokine reduction. In humans, aromatherapy (from 15 to 30 min) does not appear to be useful in order to reduce stress, anxiety, and nausea, compared to placebo. Compared to baseline, BE topical application and BEO aromatherapy reduce blood diastolic and systolic pressure and could have a significant effect on improving mental conditions. Abstract : We performed a systematic review of 31 studies regarding the effects of bergamot derivatives (extract, juice, essential oil, polyphenolic fraction) on lipid profile, glycemic status, skin, bone, and mental health. The results of this our support the efficacy of Bergamot as a modulator of lipid profile. Compared to placebo, bergamot aromatherapy does not appear to be useful in order to improve mental health. As regards the other aspects, the data are not sufficient to express a definitive indication.